Study of the national Albanian poet 'Naim Frasheri' - Ziaee, Ali Akbar (Xlibris Corporation, 2011)
Naim Frasheri (1846-1900) is the most famous poet of the Albanian renaissance of the nineteenth century. He is nowadays widely considered to be the national poet Albanian. The significance of Naim Frasheri as a national poet rest upon mystical and religious messages it transmitted to the Muslims in general and to the Bektashi believers in especial. His role as a socio-political thinker in the liberation of Albania from the Ottoman conquest is of special significance. He influenced Albanian writers at the beginning of the twentieth century enormously. many of his poems were set to music during his lifetime and were sung as folk songs in national celebrations or Bektashi songs in the religious ceremonies such as Sultan Novruz on March 21. My presentation will focus on the role of Naim Frasheri in the formation of islamic Mystical literature in Albania.